Features of designing evacuation exits in the reconstruction of civil protection shelters for public buildings - Filonenko , Olena; Tokar, Bohdan; Aniskin, Aleksej (Academic journal Industrial Machine Building Civil Engineering, 2024)
In the context of the war in Ukraine, the issue of public safety has become acute. Civil protection measures include designing shelters or reconstructing existing basements. A component of the basement reconstruction is the redevelopment of evacuation exits from the shelters. The relevant current regulatory framework is analyzed. The object of the study is the building of an educational institution in the city of Poltava, built in the 19th century. A project for reconstructing the basement into a dual-purpose room with a separate emergency exit outside the building collapse zone has been developed.